Differential Expression and Roles of Secreted Frizzled-Related Protein 5 and the Wingless Homolog Wnt5a in Periodontitis. (May 2017) - Maekawa, T.; Kulwattanaporn, P.; Hosur, K.; Domon, H.; Oda, M.; Terao, Y.; Maeda, T.; Hajishengallis, G.
The Wingless/integrase-1 (Wnt) family of protein ligands and their functional antagonists, secreted frizzled-related proteins (sFRPs), regulate various biological processes ranging from embryonic development to immunity and inflammation. Wnt5a and sFRP5 comprise a typical ligand/antagonist pair, and the former molecule was recently detected at the messenger RNA (mRNA) level in human periodontitis. The main objective of this study was to investigate the interrelationship of expression of Wnt5a and sFRP5 in human periodontitis (as compared to health) and to determine their roles in inflammation and bone loss in an animal model. We detected both Wnt5a and sFRP5 mRNA in human gingiva, with Wnt5a dominating in diseased and sFRP5 in healthy tissue. Wnt5a and sFRP5 protein colocalized in the gingival epithelium, suggesting epithelial cell expression, which was confirmed in cultured human gingival epithelial cells (HGECs). The HGEC expression of Wnt5a and sFRP5 was differentially regulated by a proinflammatory stimulus (lipopolysaccharide [LPS] from Porphyromonas gingivalis ) in a manner consistent with the clinical observations (i.e., LPS upregulated Wnt5a and downregulated sFRP5). In HGECs, exogenously added Wnt5a enhanced whereas sFRP5 inhibited LPS-induced inflammation, as monitored by interleukin 8 production. Consistent with this, local treatment with sFRP5 in mice subjected to ligature-induced periodontitis inhibited inflammation and bone loss, correlating with decreased numbers of osteoclasts in bone tissue sections. As in humans, mouse periodontitis was associated with high expression of Wnt5a and low expression of sFRP5, although this profile was reversed after treatment with sFRP5. In conclusion, we demonstrated a novel reciprocal relationship between sFRP5 and Wnt5a expression in periodontal health and disease, paving the way to clinical investigation of the possibility of using the Wnt5a/sFRP5 ratio as a periodontitis biomarker. Moreover, we showed that sFRP5 blocks experimental periodontal inflammation and bone loss, suggesting a promising platform for the development of a new host modulation therapy in periodontitis.